Justice without the Rule of Law? The Challenge of Rights-Based Industrial Relations in Contemporary Cambodia - Adler, Daniel; Woolcock, Michael (World Bank, Washington, DC, 2014)
A significant proportion of the world's work is done in contexts where the rule of law is absent or severely lacking. This paper describes one such context, that of contemporary Cambodia. Based on a literature review and interviews with key informants the authors find that there are opportunities to embed labor markets in regulatory frameworks, even at the periphery of the global economy. In such contexts, however, it is suggested that orthodox models of legal and judicial reform, which focus on drafting better laws and building capacity in judicial and administrative institutions for their enforcement, may not be the most effective way forward. Rather, the Cambodian experience suggests that the following were crucial in moving towards better protection of workers' rights: understanding the limitations of law as an instrument for attainment of rights absent independent and accessible judicial institutions; confronting the barriers to the establishment of such institutions (and being open to alternative strategies); recalling that law can have a powerful normative force, even without direct enforcement; engaging with the way in which rights are attained through processes of social contest; and supporting institutional forums for such contests to be played out in ways which maximize the potential for the disadvantaged to take part and tap in to the legitimating power of the law.